1992
DOI: 10.1071/ar9921711
|View full text |Cite
|
Sign up to set email alerts
|

Using the n-alkanes of plant cuticular wax to estimate the species composition of herbage mixtures

Abstract: This study examined whether or not between-species differences in the concentrations of saturated hydrocarbons (n-alkanes) in the cuticular wax of pasture species could be exploited to estimate the species composition of herbage mixtures. Six sets of mixtures were prepared, containing either two, three or four species. The levels of cuticular wax alkanes were estimated in samples of the pure species and the mixtures, and used in simultaneous equations to compute species composition. The levels of Lolium perenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 17 publications
2
44
0
11
Order By: Relevance
“…Plant wax profiles of the forages and CSM We have reported elsewhere on the alkane profiles of the diet components in the present study (Charmley and Dove, 2007) and drawn attention to the fact that the low alkane concentrations in phalaris, whilst typical of the species (Dove, 1992), made it difficult to estimate diet composition and forage intake in diets containing large proportions of this species. By contrast, LCOH concentrations in the diet components were much higher than their alkane concentrations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Plant wax profiles of the forages and CSM We have reported elsewhere on the alkane profiles of the diet components in the present study (Charmley and Dove, 2007) and drawn attention to the fact that the low alkane concentrations in phalaris, whilst typical of the species (Dove, 1992), made it difficult to estimate diet composition and forage intake in diets containing large proportions of this species. By contrast, LCOH concentrations in the diet components were much higher than their alkane concentrations.…”
Section: Discussionmentioning
confidence: 87%
“…Further investigation suggested that this had occurred as a result of the strong correlation between the LCOH profiles of the phalaris and ryegrass (r 5 0.989). Dove (1992) presented data indicating that, whilst it was difficult to distinguish subterranean clover and lucerne in herbage mixtures because their alkane profiles were highly correlated, total legume content of the mixtures was well estimated. By analogy in the present study, we recalculated the diet composition of sheep consuming Diet 4 based on the LCOH profiles of CSM, subterranean clover and a 'total grass' fraction.…”
Section: Estimation Of Diet Compositionmentioning
confidence: 99%
“…The diet composition was estimated according to Dove and Mayes (1991) and Dove (1992) using alkane profile (fingerprint) of faeces for each sheep and the profiles of the individual component of t h e diet. Diet composition was calculated using software "Eatwhat" established by Dove and Moore (1995) based on least-squares optimization procedure.…”
Section: Methodsmentioning
confidence: 99%
“…A composição de espécies forrageiras disponíveis para o pastejo é uma característica importante nos estudos nutricionais, especialmente em pastagens consorciadas que possam proporcionar melhor desempenho animal com a presença de leguminosas ou em pastagens com maior proporção de leguminosas (Dove, 1992).…”
Section: Introductionunclassified
“…Entre as metodologias existentes, Dove & Mayes (1999) destacaram o uso dos indicadores naturais presentes nas plantas, os n-alcanos, pois não prejudicam a saúde dos animais ou do homem e possibilitam estimativas acuradas da ingestão de MS e da composição botânica das dietas consumidas pelos animais.…”
Section: Introductionunclassified